STUDENTS’ KNOWLEDGE BEFORE AND AFTER EMERGENCY RESPONSE SIMULATION AND ITS RELATIONSHIP WITH SATISFACTION AT ISLAMIC BOARDING SCHOOL IN MALANG, EAST JAVA - Qomariyatus Sholihah; Dewi Hardiningtyas; Astuteryanti Tri Lustyana (Badan Penerbit Jurnal, Faculty of Engineering, Universitas Brawijaya, 2019)
Malang city, East Java has several modern Islamic boarding schools that carry out an integrated education curriculum between religious, national and international curricula. In order to support its education process, the schools provide modern facilities in the form of multi-storey buildings. In an Islamic boarding school, it has 6 storey buildings with a height of 3 until 5 floors that must be managed. The school also has to educate around 430 female students and 345 male students in different areas. Emergency response simulation is a crucial activity for the students not only to educate how to respond to an emergency situation but also to evaluate the protection facilities in the school. This research was conducted to identify the students’ knowledge before and after the emergency response simulation and its relationship with the satisfaction of the simulation. A descriptive research method was carried out and the data collection techniques in this study used a questionnaire with 100 respondents from female and male students. The results of the questionnaire that had been obtained were analyzed using the Structural Equation Modeling (SEM) analysis test with AMOS version 23 application. The results of SEM analysis test on the covariance table produced P-Value of <0.01; hence, there is a correlation between the Pre Test and the Post Test results. The results of the linear regression test using ANOVA showed that all independent variables (Pre Test result) have an influence on the Post Test results at 0.396 or 39.6%.